(untitled) (Research, Society and Development, 2023)
The present study aims to describe the development of a practical guide on compatibility between drugs administered in Y. This is a descriptive study of the experience report type, which was developed in the period from March to August 2022 at the University Hospital of Lagarto (HUL), based on the survey of standardized intravenous drugs in the hospital. For the development of the instrument, a narrative bibliographical review was desenvolved and consultations with guides and manuals were published by other specialized hospital units and medicine package inserts. The drugs that had incompatibilities were listed in a table, as well as those that did not present information from compatibility tests. After a careful review of the standardized items in the HUL, 123 drugs were selected to compose the Y-incompatibility guide, because they represent those with intravenous administration. The guide was structured based on the standard model of materials produced by the HUL Hospital Pharmacy Sector. For drugs with insufficient data in the literature, warnings about few tests, no tests, and mixtures with other drugs are not indicated or no information was found in the references, as appropriate. The drugs that had more data in the literature about incompatibilities were phenytoin and diazepam. With this work, it was possible to demonstrate the importance of research focusing on strategies that minimize the potential damage caused by drug incompatibility.